Diversity species and condition of seagrass ecosystem in Teluk Awur and Prawean Jepara. (February 2019) - Riniatsih, I; Ambariyanto, A; Yudiati, E; Hartati, R; Widianingsih, W; Mahendrajaya, R T
Abstract: Seagrass bed ecosystem is one of the coastal marine ecosystems which supports the health of coral reef ecosystem. The purpose of this study was to determine the diversity of species and seagrass conditions in Teluk Awur and Prawean Jepara. Nowadays, increasing land development and coastal activity highly affect the condition of seagrass bed ecosystem. This research used transects quadrant method with 100 meters length. Water quality (pH, salinity, depth and substrate) were also measured. The research result showed that there were 5 species found in both site i.e. Enhalus acoroides, Cymodocea rotundata, Cymodocea serrulata, Thalassia hemprichii, and Syringodium isoetifolium . The lowest dominance was found in Teluk Awur for the S . isoetifolium (0.65%), while the highest dominance in both research areas is C . serrulata . The seagrass coverage showed an unhealthy condition at both location (28.55% and 48.71%). Fisherman's traditional boat activities as well as fishing and trampling activities are suspected to be the main cause of the decreasing health index of seagrass bed ecosystem at both stations.